Ups and downs: The PPARγ/p-PPARγ seesaw of follistatin-like 1 and integrin receptor signaling in adipogenesis - Dongliang Fang; Xinyi Shi; Xiaowei Jia; Chun Yang; Lulu Wang; Baopu Du; Tao Lu; Lin Shan; Yan Gao (Elsevier, 2022)
Objective: Although Follistatin-like protein 1 (FSTL1), as an "adipokine", is highly expressed in preadipocytes, the detail role of FSTL1 in adipogenesis and obesity remains not fully understood. Methods: In vitro differentiation of both Fstl1−/− murine embryonic fibroblasts (MEFs) and stromal vascular fraction (SVF) were measured to assess the specific role of FSTL1 in adipose differentiation. Fstl1 adipocyte-specific knockout mice were generated to evaluate its role in obesity development. Gene expression analysis and phosphorylation patterns were performed to check out the molecular mechanism of the biological function of FSTL1. Results: FSTL1 deficiency inhibited preadipocytes differentiation in vitro and obesity development in vivo. Glycosylation at N142 site was pivotal for the biological effect of FSTL1 during adipogenesis; the conversion between PPARγ and p-PPARγ was the key factor for the function of FSTL1. Molecular mechanism studies showed that FSTL1 functions through the integrin/FAK/ERK signaling pathway. Conclusions: Our results suggest that FSTL1 promotes adipogenesis by inhibiting the conversion of PPARγ to p-PPARγ through the integrin/FAK/ERK signaling pathway. Glycosylated modification at N142 of FSTL1 is the key site to exert its biological effect.